Computational studies on sirtuins from Trypanosoma cruzi: structures, conformations and interactions with phytochemicals. - Lionel Sacconnay; Melissa Angleviel; Giuseppe Marco Randazzo; Marcos Marçal Ferreira Queiroz; Emerson Ferreira Queiroz; Jean-Luc Wolfender; Pierre-Alain Carrupt; Alessandra Nurisso (Public Library of Science (PLoS), 2014)
BACKGROUND: The silent-information regulator 2 proteins, otherwise called sirtuins, are currently considered as emerging anti-parasitic targets. Nicotinamide, a pan-sirtuin inhibitor, is known to cause kinetoplast alterations and the arrested growth of T. cruzi, the protozoan responsible for Chagas disease. These observations suggested that sirtuins from this parasite (TcSir2rp1 and TcSir2rp3) could play an important role in the regulation of the parasitic cell cycle. Thus, their inhibition could be exploited for the development of novel anti-trypanosomal compounds. METHODS: Homology modeling was used to determine the three-dimensional features of the sirtuin TcSir2rp1 from T. cruzi. The apo-form of human SIRT2 and the same structure solved in complex with its co-substrate NAD(+) allowed the modeling of TcSir2rp1 in the open and closed conformational states. Molecular docking studies were then carried out. A library composed of fifty natural and diverse compounds that are known to be active against this parasite, was established based on the literature and virtually screened against TcSir2rp1 and TcSir2rp3, which was previously modeled by our group. RESULTS: In this study, two conformational states of TcSir2rp1 were described for the first time. The molecular docking results of compounds capable of binding sirtuins proved to be meaningful when the closed conformation of the protein was taken into account for calculations. This specific conformation was then used for the virtual screening of antritrypanosomal phytochemicals against TcSir2rp1 and TcSir2rp3. The calculations identified a limited number of scaffolds extracted from Vismia orientalis, Cussonia zimmermannii, Amomum aculeatum and Anacardium occidentale that potentially interact with both proteins. CONCLUSIONS: The study provided reliable models for future structure-based drug design projects concerning sirtuins from T. cruzi. Molecular docking studies highlighted not only the advantages of performing in silico interaction studies on their closed conformations but they also suggested the potential mechanism of action of four phytochemicals known for their anti-trypanosomal activity in vitro.